AN ANALYSIS OF BUYING AND SELLING THROUGH ONLINE TRANSACTIONS PERSPECTIVE OF ISLAMIC LAW - Faruk, Ahmad; Mahmud, Mohamad (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
Abstrak Research entitled Analysis of Sale and Purchase Through Online Transactions Using the As Salam Agreement Viewed From Islamic Law (Case Study of Buying and Selling Through Online Transactions Using the AsSalam Agreement) This research is normative legal research or library law research which is prescriptive and the method of approach uses qualitative methods. Research on Islamic law through Islamic law research, research on the sale and purchase of AsSalam through online transactions conducted by students of IAI Darussalam Blokagung Banyuwangi Regency. This article is a type of qualitative research that uses descriptive analysis, which describes research data collected both from interviews, observations and research while being collected at the IAIDA Blokagung campus in Banyuwangi Regency. The results showed that basically all forms of muamalah are permissible or permissible, except as otherwise determined by the Al-Quran Sunnah and Ijma '. Buying and selling which is included in the field of muamalah and is specialized in this writing namely as-salam in terms of Islamic law is permissible or halal done with various mechanisms that exist as long as it does not conflict with the Al-Quran As-Sunnah and Ijma '. Then online transactions that are used as a medium or in this case the internet in buying and selling assalam if viewed from Islamic law is permissible as long as its use is not contrary to Islamic principles. Islamic law originating from the Islamic religion itself, views online media as permissible, not in conflict with Islamic principles. Regarding the operational use of the internet in this case, published by buying and selling greetings, further to Urf '. This is what convinces researchers that Islamic law with its three sources has provided a complete and flexible explanation of things that are updated nowadays or modern.  Keywords: Online Transactions, Islamic Law